Didong music form as a representation of Gayo community cultural identity: a synthetic ethnographic approach - Amris Albayan; Bambang Sunarto; Santosa Soewarlan; Zulkarnain Mistortoify (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2025)
This study aims to analyze Didong music form as a of cultural identity among the Gayo people of Aceh, by analyzing its instruments, melodies, rhythms, and poetry. This study employs ethnomusicology using the kualitatif etnografis method, gathering data through observation, documentation, and wawancara. The main subjects of the study are Didong and traditional figures involved in preserving Gayo cultural arts. Analysis is carried out through transcription, terbuka pengkodean, penafsiran, and cultural and musical interpretation. According to the study's findings, traditional instruments like the bantal didong and the telapak tangan (palm) create a khas rhythm that serves as the rhythms foundation for syair. Melodi didong, which employs guk, tok, gelduk, and sarik vocal techniques, conveys a strong emotional expression and creates a unique musical style. Through several beat marker rhythms such as tepok tulu, tepok bantal, tingkah pumu, tingkah bantal, and geretek enhance the character of Didong rhythms. Meanwhile, Gayo-language poetry contains cultural values, social criticism, and collective symbols of the Gayo community. These elements show that Didong music serves as both an aesthetic expression and a cultural identity for the Gayo people. This study highlights the importance of integrating music and culture analysis and creating an interdisciplinary research space on music as a social and ideological phenomenon.